The theory of taxation and public economics - Kaplow, Louis (Princeton University Press, 2011)
The Theory of Taxation and Public Economics presents a unified conceptual framework for analyzing taxation--the first to be systematically developed in several decades. An original treatment of the subject rather than a textbook synthesis, the book contains new analysis that generates novel results, including some that overturn long-standing conventional wisdom. This fresh approach should change thinking, research, and teaching for decades to come. Building on the work of James Mirrlees, Anthony Atkinson and Joseph Stiglitz, and subsequent researchers, and in the spirit of classics by A.C. Pi.